Linked lives: Gender, family relations and recurrent care proceedings in England. (October 2019) - Bedston, Stuart; Philip, Georgia; Youansamouth, Lindsay; Clifton, John; Broadhurst, Karen; Brandon, Marian; Hu, Yang
Abstract: In the wake of a "national care crisis" in England, an increasing number of parents return to the family court as repeat respondents in care proceedings and lose successive children from their care. Despite considerable progress in understanding the trends and patterns of mothers' (re)appearances in care proceedings, knowledge of fathers and of parents' family relationships in recurrent care proceedings remains very limited. Whilst such relationships are fundamentally at stake in care proceedings, they remain largely unexplored. Analyzing population-level administrative data from the family courts in England (2007/08–2017/18, N  = 25, 457 recurrent parents), we have, for the first time, uncovered a five-fold typology of family relations between mothers, fathers and children as they navigated repeated sets of care proceedings. We show that each identified profile is characterized by parents' gender as well as distinctive life-course positions of the parents and children. Our findings show that a substantial number of fathers are 'visible' in care proceedings, and that the majority of those that return to court do so with the same partners and children, as part of either a recurrent family or recurrent couple. Mothers' recurrence is characterized by their re-partnering experiences and lone appearances before the court. The results underscore the value of applying a relational approach in social work research and practice, to build a fuller picture of recurrent care proceedings. This research provides new evidence to inform the development of holistic, gender-sensitive and father-inclusive services in the English family justice system. Highlights: First national study of family relations in recurrent care proceedings in England Life-course position conditions parents' family relations in recurrent proceedings. A sizeable number of families re-appear before the English family courts. Recurrent fathers are most likely to return to court with the same partner. There is a need for whole-family, gender-sensitive services with recurrent parents.